Risk of pneumonia in patients with isolated minor rib fractures: a nationwide cohort study - Yu-Hsun Wang; Ming-Chih Chou; Sai-Wai Ho; Ying-Hock Teng; Shun-Fa Yang; Han-Wei Yeh; Chao-Bin Yeh (BMJ Open)
Objectives Isolated minor rib fractures (IMRFs) after blunt chest traumas are commonly observed in emergency departments. However, the relationship between IMRFs and subsequent pneumonia remains controversial. This nationwide cohort study investigated the association between IMRFs and the risk of pneumonia in patients with blunt chest traumas.Design Nationwide population-based cohort study.Setting Patients with IMRFs were identified between 2010 and 2011 from the Taiwan National Health Insurance Research Database.Participants Non-traumatic patients were matched through 1:8 propensity-score matching according to age, sex, and comorbidities (namely diabetes, hypertension, cardiovascular disease, asthma and chronic obstructive pulmonary disease (COPD)) with the comparison cohort. We estimated the adjusted HRs (aHRs) by using the Cox proportional hazard model. A total of 709 patients with IMRFs and 5672 non-traumatic patients were included.Main outcome measure The primary end point was the occurrence of pneumonia within 30 days.Results The incidence of pneumonia following IMRFs was 1.6% (11/709). The aHR for the risk of pneumonia after IMRFs was 8.94 (95% CI=3.79 to 21.09, p<0.001). Furthermore, old age (≥65 years; aHR=5.60, 95% CI 1.97 to 15.89, p<0.001) and COPD (aHR=5.41, 95% CI 1.02 to 3.59, p<0.001) were risk factors for pneumonia following IMRFs. In the IMRF group, presence of single or two isolated rib fractures was associated with an increased risk of pneumonia with aHRs of 3.97 (95% CI 1.09 to 14.44, p<0.001) and 17.13 (95% CI 6.66 to 44.04, p<0.001), respectively.Conclusions Although the incidence of pneumonia following IMRFs is low, patients with two isolated rib fractures were particularly susceptible to pneumonia. Physicians should focus on this complication, particularly in elderly patients and those with COPD.